Disciplining the Rich: Tocqueville on Philanthropy and Privilege. Issue 3 (2021) - Avramenko, Richard; Wolf, Brianne
Abstract: This article inquires into the moral successes and failings of the superrich in America. To do this, we turn to Alexis de Tocqueville who outlines a set of expectations for any privileged elite. Drawing from his Old Regime, Memoir on Pauperism, and Democracy in America, we argue that the superrich are obliged to a particular kind of charity, which we specify as philanthropy. To fulfill their philanthropic duties, the superrich must steadfastly attend to three obligations: maintaining their local communities, safeguarding local liberties, and providing moral leadership. In the conclusion, we suggest how the superrich might be disciplined unto this virtue.